Electrochemically Triggered Metal–Insulator Transition between VO2 and V2O5. (25th June 2018) - Lu, Qiyang; Bishop, Sean R.; Lee, Dongkyu; Lee, Shinbuhm; Bluhm, Hendrik; Tuller, Harry L.; Lee, Ho Nyung; Yildiz, Bilge
Abstract: Distinct properties of multiple phases of vanadium oxide (VO x ) render this material family attractive for advanced electronic devices, catalysis, and energy storage. In this work, phase boundaries of VO x are crossed and distinct electronic properties are obtained by electrochemically tuning the oxygen content of VO x thin films under a wide range of temperatures. Reversible phase transitions between two adjacent VO x phases, VO2 and V2 O5, are obtained. Cathodic biases trigger the phase transition from V2 O5 to VO2, accompanied by disappearance of the wide band gap. The transformed phase is stable upon removal of the bias while reversible upon reversal of the electrochemical bias. The kinetics of the phase transition is monitored by tracking the time‐dependent response of the X‐ray absorption peaks upon the application of a sinusoidal electrical bias. The electrochemically controllable phase transition between VO2 and V2 O5 demonstrates the ability to induce major changes in the electronic properties of VO x by spanning multiple structural phases. This concept is transferable to other multiphase oxides for electronic, magnetic, or electrochemical applications. Abstract : An electrochemically triggered phase transition between VO2 and V2 O5 is revealed by using in situ ambient‐pressure X‐ray spectroscopic tools. The stoichiometry‐driven phase transition is achieved by using both a solid electrolyte (yttria‐stablized zirconia) at elevated temperature and ionic liquid at room temperature. A drastic change in electronic structure of VO x is found accompanying the phase transition.